An Analysis of Code Switching in Leila S. Chudori’s For Nadira - Lusiana Kartika Candra; Laila Ulsi Qodriani (TEKNOSASTIK, 2018)
This research focused on analysis of types and reasons of using code switching by the characters in For Nadira novel. The writers applied Hoffman theory which functioned to categorize the types of code switching, and Holmes which functioned to explain the reason why the speakers do code switching. Besides, this research also adopted qualitative method, since the analysis dealt with words instead of numbers. The results of the analysis showed that there are four types of code switching occurred in For Nadira novel. Those are intra-sentential switches, inter-sentential switches, establishing continuity switches, and emblematic switching. Then, there are seven reasons influenced the characters in For Nadira novel switch their language. Those are to assert power, pride and status, to declare the solidarity, to express ethnic identity, to express self-emotion, to being more competence, to being more informative and to convey the speaker’s attitude to the listener.Key Words: Code switching, For Nadira, reason, sosiolinguistics, types